Employee Performance In Light Of Work Stress And Environment - Harahap, Muhammad Ade Kurnia; Yudiani, Ema; Erna, Erna; Nururly, Santi (Program Pascasarjana STIE Amkop Makassar, 2023)
Employee is end spear walk wheel company , so that study This aim analyze performance employees at PT. Baroque Son of West Java . reviewed from pressure work and environment Work against . Study descriptive quantitative This involved 69 respondents through questionnaire with Likert scale . Data analysis was performed use SPSS for test validity , reliability questionnaire , And test hypothesis . Results study show (1) pressure work have impact negative on performance employees at PT. Baroque Son of West Java ., (2) environment Work have impact positive on performance employees at PT. Barokah Putra Jabar and (3) By Simultaneously , pressure work and environment Work impact positive and up performance employee in PT. Baroque Son of West Java . Researcher recommend company notice pressure work And environment Work for progress company in every period. Keywords: Performance , Stressed Work , Environment Work